Extended Temporary Arrest - Kalaba, Dragan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Having the Constitution of Serbia in mind, valid criminal legislature (Criminal Law and the Law of criminal procedure), the working basis of the competent state authorities is their legislature (legality). Unfortunately, this is not often the case. So in the case of the temporary arrest obtaining accused to the court proceeding, there must not be any dilema, because it is one of delicate institutions of criminal law. In the previously mentioned examples, according to our opinion, there is a breaking of Law because previously defined or extended temporary arrest is „shortened“, for a few days by the new decision. That is why we expect the Court of Cassation to observe existing laws and regulations, as it is shown above.